Carps polyculture technique in Mohanpur, Rajshahi region of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
The present study was undertaken with a view to finding out the carps poly-culture technique, pond management and cost analysis in Mohanpur, Rajshahi region of Bangladesh. The study was conducted for a period of four months (October 2010 to February 2011). It provides an overview on the guiding principles, aspects and tasks, and presents the applicable production techniques and patterns of carp polyculture. It is expected that this publication will help identify resources and contribute to the successful planning and realization of fish production by those fish pond owners and operators who need to strengthen and improve their knowledge on the subject.Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 100-105